Stability Analysis of a Fractional-Order Digital Control System - Purnima, D. Naga; Deekshitulu, G.V.S.R.; Ramana, G.V.; Prabhakar, M. Bala (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper presents a new framework for analyzing the stability of fractional-order digital control systems (FODCS) utilizing the N-transform method. In contrast to conventional techniques that rely on Laplace or Grunwald–Letnikov formulations, the proposed approach supports discrete-time modeling and allows for the visualization of stability regions through Riemann surface decomposition. The method derives closed-form unit step responses and introduces generalized stability criteria applicable to both linear and nonlinear systems. A comparative analysis with existing methods demonstrates improved interpret ability and computational efficiency, making this approach a valuable asset for advanced digital control applications.